(untitled) (The Review of Diabetic Studies, 2025)
Advanced nursing roles have become increasingly integral to modern healthcare systems as a response to rising clinical complexity, workforce shortages, and the demand for high-quality, patient-centered care. These roles extend beyond traditional bedside functions to encompass advanced clinical practice, education, leadership, and system-level decision-making. This review aims to synthesize current evidence on the impact of advanced nursing roles on healthcare delivery, with a particular focus on clinical, educational, and leadership contributions. A comprehensive review of the literature was conducted across major healthcare databases, including peer-reviewed studies published between 2016 and 2025. Findings indicate that advanced nursing roles are consistently associated with improved patient outcomes, enhanced care coordination, reduced hospital length of stay, and increased patient satisfaction. In addition, advanced nurses play a critical role in workforce development through clinical education, mentoring, and knowledge translation, thereby strengthening professional competencies and evidence-based practice. At the organizational level, their leadership contributions support clinical governance, interprofessional collaboration, and healthcare system resilience. Overall, the evidence highlights advanced nursing roles as a strategic asset in optimizing healthcare delivery. Strengthening policy support, role clarity, and educational pathways is essential to fully leverage their potential and ensure sustainable health system performance.